O uso da internet como ferramenta de apoio ao esclarecimento de dúvidas durante a gestação The use of the Internet as a support tool to clarify questions during pregnancy - Calderon, Taiara Maestro; Cestari, Maria Elisa Wotzasek; Dobkowski, Alyni Cristiny; Cavalheiro, Mariana Digieri (Journal of Health & Biological Sciences, 2016)
Introduction: Pregnancy is a period of doubts and anxiety for most pregnant women. Objective: To evaluate the use of the Internet as a support tool to clarify doubts raised by women during pregnancy. Methods: An exploratory and descriptive study. Sample based on accidentalness, for 241 users who responded to the on-line form, built with Google Docs and made available in one Blog. Results: 98% of pregnant women were between 19 and 39 years, 97% with schooling above 9 years, 99% had follow up with healthcare providers. Regarding the use of the Internet, 99% said they usually search for the pregnancy questions. The doubts consisted mostly in the search for information about the development of the baby, then how to deal with the discomforts of pregnancy, the changes in the woman’s body and feeding care. The choice of the sites, according to the interviewees, occurred mainly through the indication of social networks, friends and acquaintances. Regarding to the resolution of doubts, 97% reported that after the Internet search doubts were resolved. Conclusion: The Internet has been a tool of support for pregnant women who seek effective support on the World Wide Web to clarify their doubts. The significant standard for clarification and education reflected a customer that will search and possibly question the procedures and practices that are performed during prenatal care. However, the search for sites has been based on independent research guidance by health professionals, something which does not ensure the credibility of the sites surveyed by users.